CORRELATION OF PRICE AND PRESTIGE VALUE ON THE PURCHASE OF GOLD JEWELRY IN REJANG LEBONG DISTRICT DURING THE FASTING MONTH - Pefriyadi, Pefriyadi; Nur, Ardiles (Multifinance, 2024)
This study aims to understand the factors influencing consumer purchasing decisions, specifically in the context of buying gold jewelry during Ramadan in the Rejang Lebong Regency. Ramadan often serves as a significant time for purchasing gold jewelry as a religious, cultural symbol, and investment. The study investigates the relationship between price and prestige value in the purchase decisions of gold jewelry. Data was collected through questionnaires distributed to 100 consumers who bought gold jewelry during Ramadan 2024 using a purposive sampling method. Additionally, structured interviews were conducted to gain deeper insights. Data analysis was performed using simple linear regression to test the relationship between price and prestige value on purchase decisions. The results indicate a significant relationship between price and prestige value with consumer purchase decisions. This suggests that price and prestige value directly influence consumer purchase decisions during Ramadan in Rejang Lebong. These findings are consistent with economic theories stating that price and prestige value are important factors in decision-making. The implications of these results highlight the importance of marketing strategies that consider these factors to attract consumers.